1994
DOI: 10.2166/wst.1994.0324
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Approaches for the Characterisation of a Nitrification/Denitrification Process on Industrial Wastewater

Abstract: Laboratory experiments were carried out to evaluate the feasibility of the biological removal of nitrogen from mixed textile (80%) and municipal (20%) wastewater. Three modified “Ludzack Ettinger” bench scale plants were used. Wastewater characterization and process kinetic constants were evaluated experimentally. The results of this experience demonstrated that long sludge age is necessary in order to overcome the nitrification inhibitory effect of some compound(s) that were present in the treated wastewater.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…As organic carbon removal kinetics relates to soluble carbonaceous materials in those models, special attention was paid to the extent to which this part of organic matter could be biologically removed from petrochemical wastewater. As mentioned earlier, the method applied to this end comprised of physical tests and bioassay, based on the same assumptions as those presented by other authors (Bortone et al, 1994;Dold et al, 1986;Mamais et al, 1993;Mbewe et al, 1995;Trela, 2000;Vanhooren, 2002;Wentzel et al, 1999). The main assumption of this method is that, for a steady-state ASFBBR bioreactor, most of the readily-biodegradable fraction of COD in the wastewater is consumed by biomass.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As organic carbon removal kinetics relates to soluble carbonaceous materials in those models, special attention was paid to the extent to which this part of organic matter could be biologically removed from petrochemical wastewater. As mentioned earlier, the method applied to this end comprised of physical tests and bioassay, based on the same assumptions as those presented by other authors (Bortone et al, 1994;Dold et al, 1986;Mamais et al, 1993;Mbewe et al, 1995;Trela, 2000;Vanhooren, 2002;Wentzel et al, 1999). The main assumption of this method is that, for a steady-state ASFBBR bioreactor, most of the readily-biodegradable fraction of COD in the wastewater is consumed by biomass.…”
Section: Resultsmentioning
confidence: 99%
“…Correctness of the above assumption is justified by the methodology and results of similar studies for municipal wastewater published by other authors (Bortone et al, 1994;Dold et al, 1986;Mamais et al, 1993;Mbewe et al, 1995;Wentzel et al, 1999). This was also proved during respirometric tests and conducted simulations of the ASFBBR reactor's organic carbon removal kinetics (Trojanowicz and Wojcik, 2011;Trojanowicz et al, 2009).…”
Section: Determination Of a Readily Biodegradable Fraction Of Codmentioning
confidence: 85%
“…The two‐sludge process proved efficient and reliable while treating high strength wastewater from a urea plant,12 pig farm wastewater,13 and other industrial discharges 14. High rates of nitrification and denitrification were reported to be achieved for ammonia concentrations in the influent up to 5000 mg N‐NH 3 dm −3 , in which no organic load was present and careful pH control was ensured15 to avoid inhibition by free ammonia. A disadvantage of a two‐stage nitrification/denitrification is, however, a need for an external carbon source, necessary to sustain the denitrification requirement for reduced compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Even if the single‐sludge process performs well when applied for a full‐scale treatment of domestic wastewater,1 instability of nitrification can be a serious problem while treating wastewater of industrial origin, as shown, for example, by Bortone et al 15 in their study on nitrification/denitrification of textile wastewater. To overcome the inhibitory effect on nitrification exercised by compounds present in textile wastewater, a long sludge age and high temperature (30 °C) were necessary.…”
Section: Introductionmentioning
confidence: 99%
“…많은 차이를 보인다 (Gil, 2006;Im and Gil, 2011 (Bortone et al, 1993;Dricks et al, 1999;Ekama et al, 1986). 이를 위해 많은 연구진들이 하수 내 유기물 분류에 관 한 연구를 수행하고 있으나 연구 대상이 한정적이라는 단점이 있다 (Choi et al, 2003;Hong et al, 2003;Wentzel et al, 1999 …”
unclassified